2019
DOI: 10.1002/adma.201904535
|View full text |Cite
|
Sign up to set email alerts
|

Nanotherapy in Joints: Increasing Endogenous Hyaluronan Production by Delivering Hyaluronan Synthase 2

Abstract: Osteoarthritis (OA) is a common joint degenerative disease that causes pain, joint damage, and dysfunction. External hyaluronic acid (HA) supplement is a common method for the management of osteoarthritis which requires multi‐injections. It is demonstrated that biodegradable mesoporous silica nanoparticles successfully deliver an enzyme, hyaluronan synthase type 2 (HAS2), into synoviocytes from the temporomandibular joint (TMJ) and generate endogenous HA with high molecular weights. In a rat TMJ osteoarthritis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 37 publications
1
42
0
Order By: Relevance
“…Nowadays, nanomaterials have been widely applied in the field of bone regeneration, [ 21–24 ] since they possess several outstanding advantages, such as large surface area‐to‐volume ratio, higher reactivity, and easy surface modification. [ 25 ] Carbon dots (CDs), a new type of fluorescent nanomaterial, [ 26,27 ] display unique properties of small size, facile preparation, low cost, good biocompatibility, and excellent optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, nanomaterials have been widely applied in the field of bone regeneration, [ 21–24 ] since they possess several outstanding advantages, such as large surface area‐to‐volume ratio, higher reactivity, and easy surface modification. [ 25 ] Carbon dots (CDs), a new type of fluorescent nanomaterial, [ 26,27 ] display unique properties of small size, facile preparation, low cost, good biocompatibility, and excellent optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…For a long time, as a representative of inorganic aerogels, silica aerogels have been widely studied and applied because of their low cost and good structure and properties [7,8]. In the field of biomedicine, previous studies have shown the diffusion mechanism of drugs in silica aerogels [9,10], and that silica nanoparticle-loaded drugs have had good targeted therapeutic effects on diseases [11,12]. In recent years, considering the degradability of materials, scientists have turned their attention to the development of natural polymers [13].…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the therapeutic system based on nanoparticles with the capabilities of regulating the OA microenvironment can intelligently enter the targeted cells and thereby efficiently suppress inflammation and delay the progression of OA. Li et al have demonstrated that polyethyleneimine-modified mesoporous silica nanospheres can successfully bring hyaluronan synthase type 2 into synoviocytes to synthesize endogenous HA with high molecular weight and downregulate the synovial inflammatory mediators in the OA microenvironment, hence promoting the self-repairing mechanism and putting forward a totally different method for OA management [ 258 ]. Chen et al designed a novel MMP-13/pH-responsive and cartilage-targeting ferritin nanocages encapsulating hydroxychloroquine for OA imaging and therapy, which can smartly monitor the overproduced MMP-13 in OA and release hydroxychloroquine induced by weak acid.…”
Section: Chronic Inflammation-associated Diseases and Therapiesmentioning
confidence: 99%